Institutional Cooperation in the Brownfield Regeneration Process: Experiences from Central and Eastern European Countries - Perić, Ana (European Spatial Research and Policy, 2016)
The topic of brownfield regeneration has been the focus of planning debate for years. However, the aspect of institutional cooperation and strengthening the institutional capacity in order to cope with a complex task of brownfield regeneration is considered a challenge. This is particularly true for the post-socialist countries and, hence, the Czech Republic, Hungary and Serbia are chosen as the case studies of this research. By implementing a concise survey of both the institutions and policies related to the topic of brownfield regeneration in the selected countries, the research aims at determining the form, extent and nature of collaboration between different sectors, disciplines, and institutions. Based on such insights, it is finally possible to provide the recommendations for more effective institutional design within specific political and socio-economic context.